Aggregation-prone A53T mutant of α-synuclein exaggerates methamphetamine neurotoxicity in SH-SY5Y cells: Protective role of cellular cholesterol. (2022) - Aoki, Sho; Funakoshi, Takeshi; Aki, Toshihiko; Uemura, Koichi
Abstract: The aim of this study is to examine the effects of wild type as well as a mutant (A53T) form of α-synuclein (α-syn) on neuronal cells exposed to methamphetamine (METH). SH-SY5Y human dopaminergic neuronal cells stably expressing exogenously added wild type (WT) or A53T α-syn were established for this purpose. Among the three types of cells, parental, WT α-syn-overexpressing, and A53T α-syn overexpressing SH-SY5Y cells (hereafter referred to as SH-SY5Y, WT SH-SY5Y, and A53T SH-SY5Y, respectively), only A53T SH-SY5Y cells showed significant loss of cell viability after exposure to 2 mM METH for 24 h. Transcriptome analysis using DNA microarray showed that METH induced genes for cholesterol biosynthesis in all of these three cell lines, suggesting that METH upregulates cellular cholesterol biosynthesis independently from cellular α-syn levels. Visualization of the cellular localization of free cholesterol showed that METH induces an aberrant intracellular accumulation of free cholesterol in all three cell lines. In addition, we observed the aggregation of α-syn into cytoplasmic granules, which was more apparent with A53T α-syn than WT α-syn, in cells exposed to METH. Furthermore, the cell death observed in METH-treated A53T SH-SY5Y cells was exaggerated by the addition of 2-hydroxypropyl-β-cyclodextrin (CD), a substance used to extract cholesterol from cells. These results suggest that the aggregation of A53T α-syn in METH-treated cells should be involved in cell death. The upregulation of cellular biosynthesis and cholesterol accumulation by METH should play a protective role against A53T α-syn neurotoxicity in METH-treated SH-SY5Y cells. Graphical Abstract: ga1 Highlights: METH induced A53T α-synuclein aggregation in neuronal cells. METH also induced cholesterol biosynthesis. Cholesterol accumulation ameliorated A53T α-synuclein neurotoxicity.